2022
DOI: 10.1186/s12916-022-02499-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of prediction models for gestational diabetes treatment modality using supervised machine learning: a population-based cohort study

Abstract: Background Gestational diabetes (GDM) is prevalent and benefits from timely and effective treatment, given the short window to impact glycemic control. Clinicians face major barriers to choosing effectively among treatment modalities [medical nutrition therapy (MNT) with or without pharmacologic treatment (antidiabetic oral agents and/or insulin)]. We investigated whether clinical data at varied stages of pregnancy can predict GDM treatment modality. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Notably, many of the identified precision markers are routinely measured in clinical practice and so could be incorporated into prediction models of need for pharmacological treatment 70 , 71 . By identifying those who require escalation of pharmacological therapy earlier, better allocation of resources can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, many of the identified precision markers are routinely measured in clinical practice and so could be incorporated into prediction models of need for pharmacological treatment 70 , 71 . By identifying those who require escalation of pharmacological therapy earlier, better allocation of resources can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In this field, the use of artificial intelligence has been tested to enhance the prediction and diagnosis of significant complications of diabetes leading to adverse cardiovascular events 20 . This is of particular interest in the field of gestational diabetes and recent research has identified the possibility of using a dedicated machine learning approach to improve its prediction 21 …”
Section: Artificial Intelligence In Cardiovascular Preventionmentioning
confidence: 99%
“…20 This is of particular interest in the field of gestational diabetes and recent research has identified the possibility of using a dedicated machine learning approach to improve its prediction. 21 In the management of dyslipidaemia, different potential applications of artificial intelligence have been tested so far, starting from the diagnosis to the management and prognosis related to the disease. Recently machine learning modelling has been applied to big datasets to obtain more accurate predictive models for incident dyslipidaemia, taking into account monogenic or polygenic variants.…”
Section: Management Of Cardiovascular Risk Factors (Arterial Hyperten...mentioning
confidence: 99%
“…When deciding on the recommendations for universal or selective GDM screening it is necessary to define the population that should be screened, the recommended screening methods and their timing, as well as the treatment modalities and the follow-up [7].…”
Section: Selective Screening Approachmentioning
confidence: 99%